Gratitude and Resilience of Young Adults: Examining the Mediating Role of Optimism and Social Support - Nahar, Nasrin; Parvin, Masuma; Begum, Farjana (European Journal of Applied Sciences, 2023)
The present study explored the mediating effect of social support and optimism in the relationship between gratitude and resilience of young adults. To achieve this objective, a package of questionnaire consisting of Gratitude Questionnaire, Revised Life Orientation Test-Revised, Social Support Questionnaire, and Resilience Scale for Adults were administered to a convenience sample of 315 students of Bangabandhu Sheikh Mujibur Rahman Science and Technology University, Gopalgonj. Their ages ranged from 19 through 26 with a mean age being 22.72 years (SD = 1.23). The results of independent sample t test reveals that there is no significant gender difference between male and female in social support number, optimism and resilience except support satisfaction and gratitude. Results of Pearson-product moment correlation reveals that gratitude, social support, optimism and resilience are correlated with one another. Findings of multiple regression analysis confirm the predictive role of support satisfaction, gratitude and optimism on resilience. Hierarchical multiple regression analysis confirms the partial mediating effect of optimism and rejects the mediating role of social support in the relationship between gratitude and resilience of young adults.